Stakeholder management in the local government decision-making area : evidences from a triangulation study with the English local government - Gomes, Ricardo Corrêa (2006)
Publicado também na Revista de Administração Contemporânea, v. 10, p. 77-98, 2006. Disponível em: <http://www.scielo.br/pdf/rac/v10nspe/v10nspea05.pdf>